The relationship between energy consumption and economic growth: a Status Report - TATOU, Fatima Zahraa; YOUSFI , Abdellah (International Journal of Economic Studies and Management (IJESM), 2022)
Since the oil crisis, and in most industrialized countries, energy management has become a topic that attracts their interest, in order to understand the type of the relationship that exists between energy consumption and the growth of GDP. Moreover, such an interest becomes more important, for economies which are essentially based on the use of energy, therefore any energy policy can have an effect on economic growth. In addition, the main objective of this work is to compare and identify the different theoretical and conceptual aspects of the results concerning the studies that have examined the causal relationship between energy consumption and economic growth for several African countries and mainly Morocco, during different periods. These different studies were based on different econometric methods depending on the type of data used and the vision of each author, so we will try to determine for each work: the country concerned, the study period, the method used and the results obtained. This diversification between these works has made the results very different, and this discrepancy is perhaps mainly due to the method used: time series, panel data, the bi-variate approach where the work is carried out with only two variables (energy consumption and GDP) or the multi-variate approach (the addition of other variables that can influence GDP or energy consumption). In addition, the sample size or the choice of years can play a role in this difference between the results. Such as, for two different studies carried out on the same country, we can find contradictory results. Therefore, the choice of the years or the method adopted has a direct impact on the result obtained.